DETERMINAN POLA PANGAN HARAPAN PADA RUMAH TANGGA BURUH PENGASIN IKAN DI PULAU PASARAN - Aneftasari, Ica Rizki; Arifin, Bustanul; Indriani, Yaktiworo (Jurnal Ilmu-Ilmu Agribisnis, 2016)
This research aims to know the household income, the distribution of food expenditure, the score of Desirable Dietary Pattern (DDP), and to analyze the determinant of householdâs DDP of fish salting labor.Â  The study was conducted in Pasaran Island, Teluk Betung Timur Sub Districts of Bandar Lampung City.Â  The total samples were 50 fish salting labor drawn by simple random sampling method.Â  The data were collected in June to August 2015 and analyzed by qualitative and quantitative analysis.Â  The data of household nutritional intake were collected by 2x24 hours food recall. Â The DDP score was counted by measuring the energy contents of each food groups consumed by labor households then compared to the recommended dietary allowance and multiply by the weight of each food group.Â  This research results showed that the household income of fish salting labor in Pasaran Island was derived from salting labor activities and non-salting labor activities with an average income of Rp36,697,428.56 per year.Â  The average food expenditure of fish salting labor in Pasaran Island was Rp22,971,080.00 per year.Â  The DDP score of fish salting labor household in Pasaran Island was 74.38, this was below the DDP score of Bandar Lampung City (80.60).Â  The DDP determinant of fish salting labor household was income, food expenditure, the age of husband,the wifeâs education and nutrition knowledge.Key words: consumption, Desirable Dietary Pattern, determinant